2021
DOI: 10.1038/s41467-021-25833-8
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the persistence and control of Rift Valley fever virus in a spatially heterogeneous landscape

Abstract: The persistence mechanisms of Rift Valley fever (RVF), a zoonotic arboviral haemorrhagic fever, at both local and broader geographical scales have yet to be fully understood and rigorously quantified. We developed a mathematical metapopulation model describing RVF virus transmission in livestock across the four islands of the Comoros archipelago, accounting for island-specific environments and inter-island animal movements. By fitting our model in a Bayesian framework to 2004–2015 surveillance data, we estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 62 publications
(75 reference statements)
0
21
0
Order By: Relevance
“…Here, we highlight that theoretical and applied models can use different tools to contribute to a common objective. In 3 cases, parameter estimations were used further in the same model to help anticipate [48] or control [47,60] outbreaks, as a secondary objective. Fifty-five percent of models provided an estimation of a type of reproduction number (e.g., the basic reproduction number R O , the effective reproduction number R e , the seasonal reproduction number R st (phenomenological relationship estimated between environmental parameters and transmission rate) or the Floquet ratio R T (the expected number of cases caused by a primary case after one complete cycle of seasons [80]), most of which were obtained analytically (25/27).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Here, we highlight that theoretical and applied models can use different tools to contribute to a common objective. In 3 cases, parameter estimations were used further in the same model to help anticipate [48] or control [47,60] outbreaks, as a secondary objective. Fifty-five percent of models provided an estimation of a type of reproduction number (e.g., the basic reproduction number R O , the effective reproduction number R e , the seasonal reproduction number R st (phenomenological relationship estimated between environmental parameters and transmission rate) or the Floquet ratio R T (the expected number of cases caused by a primary case after one complete cycle of seasons [80]), most of which were obtained analytically (25/27).…”
Section: Resultsmentioning
confidence: 99%
“…Métras et al (2017) [48] suggested that import of infected livestock in 2007 was a major driver of RVF emergence in Mayotte in 2008-2010 and Gao et al (2013) [53] that a transport of only few infectious animals from Sudan to Egypt are sufficient to start an outbreak. In Grande Comore, the RVF virus seems to be able to circulate even in absence of new introduction [60].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations